Genetics driven interventions for ex situ conservation of Red Jungle fowl (Gallus gallus murghi) populations in India - Mukesh; Fernandes, M.; Han Jianlin; Sathyakumar, S. (Wiley, 2013)
Genetics driven interventions (GDI) are imperative for ex situ conservation to exhort long-term sustenance of small and isolated populations in captivity as they are more prone to an increased extinction risk due to inbreeding and genetic drift. We investigated constitutive genetic attributes of four captive Red Junglefowl (RJF) populations in India, to facilitate the prioritization of the birds to formulate an effective breeding action plan. All the four RJF populations were found to be evident of significant inbreeding but none of them had exhibited any signature of bottleneck footprints in the recent past. Bayesian cluster analysis revealed three distinct groups among the four captive RJF populations. Interestingly, birds of Kufri population were assigned together with Gopalpur as well as with Morni populations, indicating their shared genetic ancestry. Among the four populations, Morni population displayed the richest genetic attributes and was therefore presumed as a key source of genetic variation. Nine birds of Morni population were relatively pure (q-value >0.98) and carried about 50% of the total private alleles of Morni population. Thus, being the foremost reservoir of allelic diversity, these nine birds may be selected for launching alien alleles to other RJF populations to rescue their loss of genetic diversity arising from inbreeding.